Diabetic macular oedema: the effect of photocoagulation on fluorescein transport across the blood-retinal barrier. Issue 10 (1st October 2002) - Sander, B; Larsen, M; Engler, C; Moldow, B; Lund-Andersen, H
Abstract : Background/aim: The visual loss secondary to diabetic macular oedema can be controlled to some extent by photocoagulation, though the mechanism of action is largely unknown. The purpose of the present study was to quantitate the effect of photocoagulation on the blood-retinal barrier using fluorescein as a tracer of passive and active transport. Methods: A prospective study of 46 eyes in 34 patients with clinically significant macular oedema (CSMO) examined by vitreous fluorometry before and 6 months after macular photocoagulation treatment. Results: In 23 eyes CSMO was not present at follow up (responding eyes), in another 23 other eyes CSMO was still present (non-responding eyes). With reference to the presence or absence of CSMO at follow up, the passive transport (permeability) for responding eyes decreased after photocoagulation in contrast with an increase in non-responding eyes; the difference between the groups at follow up was significant (p=0.03). The active transport for responding eyes decreased slightly at follow up, while it increased for non-responding eyes; the difference between the groups at follow up was not significant (p=0.09). Conclusion: Following photocoagulation a reduction of diabetic macular oedema, defined as disappearance of CSMO, is paralleled by a decrease of the passive permeability while the hypothesis of an increase in the active transport from the retina to the blood could not be supported by this study.